Real-Time Trajectory Planning and Control for Constrained UAV Based on Differential Flatness - Dongli Wu; Hao Zhang; Yunping Liu; Weihua Fang; Yan Wang (International Journal of Aerospace Engineering)
The trajectory planning of UAV with nonholonomic constraints is usually taken as differential algebraic equation to solve the optimal control problem of functional extremum under the condition of inequality constraints. However, it can be challenging to meet the requirements of real-time for the high complexity. A differential flat theory based on B-spline trajectory planning can replace the optimal control problem with nonlinear programming and be a good means to achieve the efficient trajectory planning of an UAV under multiple dynamic constraints. This research verifies the feasibility of this theory with actual flight experiments.